Young Man with Hepatomegaly: A Case of Glycogenic Hepatopathy - Walid Abboud; Saif Abdulla; Mohammed Al Zaabi; Ramzi Moufarrej (Case Reports in Hepatology)
Glycogenic hepatopathy is a rare but potentially reversible condition characterized by hepatomegaly and elevated liver enzymes occurring in poorly controlled type 1 diabetes mellitus patients and often requires a liver biopsy to confirm the diagnosis. We present the case of a young man who was admitted with diabetic ketoacidosis in the setting of poorly controlled diabetes mellitus type 1 and was noted to have significantly elevated transaminases that continued to worsen despite appropriate treatment of the diabetic ketoacidosis. A liver biopsy confirmed the diagnosis of glycogenic hepatopathy and the patient improved with diabetes control. The aim of this report is to shed light on possible causes of significant elevation of liver enzymes in patients presenting with diabetic ketoacidosis. In addition, we would like to raise awareness about the diagnosis, management, and prognosis of glycogenic hepatopathy and how to differentiate it from other hepatic conditions that have a similar presentation.